Molten-salt assisted synthesis of a high-performance oxide cathode for sodium-ion batteries: Na0.44MnO2 as a case. (30th January 2023) - Zhao, Haijun; Wu, Linrong; Tian, Jinlv; Zhang, Ding; Li, Xiaofeng; Xu, Shoudong; Chen, Liang; Yi, Qun; Dai, Kehua; Guo, Huijuan
Abstract : A unique phase transition process for the synthesis of Na0.44 MnO2 using a molten salt method. Abstract : Most layered oxide cathode materials for sodium-ion batteries (SIBs) bear large structural irreversibility upon the electrode reaction, and the rod-like Na0.44 MnO2 (NMO) has shown its specific merit of structural integrity for better electrochemical stability. In this work, molten salt chemistry is applied to attempt the synthesis of high-performance NMO. The optional treatment mainly adopts sodium chloride as the molten salt, Na2 CO3 and Mn2 O3 as the reactants, and sintering at 800 °C for 2 h, followed by water washing to obtain the product. The prepared cathode material shows an initial reversible specific capacity of 109.9 mA h g −1 at 0.1C (1C = 120 mA g −1 ) and releases about 65% of the initial discharge capacity at 20C. Furthermore, it exhibits a capacity retention rate of 85.4% after 500 cycles at 1C, indicating excellent long-term cycling stability, further verified by lasting full-cell cycling, as its capacity retention rate becomes 80.5% after 300 cycles at 1C. Through the study of intermediate phases, it is found that the rod-like NMO transforms from its Na-birnessite stage. This work provides an efficient and straightforward molten salt preparation process for NMO, which provides a helpful reference for applying such treatment for the universal oxide cathode materials for SIBs.